CSF β-amyloid as a putative biomarker of disease progression in multiple sclerosis. (July 2017) - Pietroboni, Anna M; Schiano di Cola, Francesca; Scarioni, Marta; Fenoglio, Chiara; Spanò, Barbara; Arighi, Andrea; Cioffi, Sara MG; Oldoni, Emanuela; De Riz, Milena A; Basilico, Paola; Calvi, Alberto; Fumagalli, Giorgio G; et al.
Background: Neurodegeneration plays a major role in determining disability in multiple sclerosis (MS) patients. Hence, there is increasing need to identify reliable biomarkers, which could serve as prognostic measure of disease progression. Objectives: To assess whether cerebrospinal fluid (CSF) tau and β-amyloid (Aβ) levels were altered in newly diagnosed MS patients and correlated with disability. Moreover, we investigated whether these CSF biomarkers associate with macroscopic brain tissue damage measures. Methods: CSF Aβ and tau levels were determined by enzyme-linked immunosorbent assay in CSF samples from 48 newly diagnosed MS patients, followed-up clinically for 3 years by recording their Expanded Disability Status Scale score at 6-month intervals, and 45 controls. All patients underwent magnetic resonance imaging at baseline and at the end of follow-up to quantify their lesion load (LL). Results: CSF Aβ levels were significantly reduced in patients compared to controls ( p  < 0.001). Lower CSF Aβ levels at baseline were a disability predictor at 3-year follow-up ( p  = 0.009). CSF tau levels correlated with T2- and T1-LL ( p  < 0.001). Conclusion: CSF Aβ reduction is a promising biomarker of neurodegeneration and may predict patients' clinical outcome. Therefore, CSF Aβ should be considered as a potential biomarker of prognostic value.